Empowering Stories: Transportation into Narratives with Strong Protagonists Increases Self-Related Control Beliefs. Issue 8 (17th November 2019) - Isberner, Maj-Britt; Richter, Tobias; Schreiner, Constanze; Eisenbach, Yanina; Sommer, Christin; Appel, Markus
ABSTRACT: Several studies have shown that narratives can influence readers' beliefs about themselves. In the present study, our goal was to investigate whether stories portraying a strong protagonist can positively influence recipients' beliefs of being in control of events in their own lives (self-related control beliefs). Experiment 1 showed that narratives in both written text and video form with protagonists displaying high versus low self-efficacy can, at least temporarily, affect recipients' own self-related control beliefs when they experience strong transportation into the stories. In addition, the results suggest that recipients' perceived ability to generate vivid mental imagery affects their transportation into and identification with characters in texts versus films. Experiment 2 manipulated transportation and identification experimentally and showed that the effect of this manipulation on self-related control beliefs was indeed mediated by experienced transportation and identification. The results are discussed within the framework of the Transportation Imagery Model of narrative persuasion.